Pengaruh Kualitas Pelayanan, Harga, Kualitas Produk, Dan Store Atmosphere Terhadap Keunggulan Bersaing Pada Usaha Resto Ayam Presto Cabe Hijo Di Kota Stabat - Ade Pratiwi (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2020)
This study aims to determine the effect of service quality, price, product quality, and store atmosphere on competitive advantage in Resto Ayam Presto Cabe Hijo Business in Stabat City. This study uses primary data obtained by distributing questionnaires to all respondents. The samples in this study are 205 respondents selected using the Purposive sampling technique. The data analysis method used is multiple linear analyses with the help of SPSS. The results of this study indicate partially that service quality has a negative influence on competitive advantage, while price, product quality, and store atmosphere have a positive effect on competitive advantage. Simultaneously, service quality, price, product quality, and store atmosphere have a positive influence on competitive advantage. From the four independent variables used in this study, only product quality has the greatest influence on competitive advantage. Keywords: Service Quality, Price, Product Quality, Store Atmosphere, Competitive advantage.